Knowledge transfer by means of university-industry collaborations: a study in UiTM / Dang Merduwati Hashim ... [et al.]. - Hashim, Dang Merduwati; Noordin, Siti Arpah; Masrek, Mohammad Norman; Abdullah Sani, Mad Khir Johari (2004)
This study aims to: (i) identify the linkages that exist between the lecturers in Ui1M and the industry, (ii) understand the motivational factors for lecturers to interact with the industry, (iii) determine what are the benefits gained by the lecturers when interacting with the industry and (iv) determine the barriers affecting the lecturers to link with the industry. Out of 700 questionnaires distributed to eighteen faculties in Ui1M, Shah Alam, which represented 10% of the total number of lecturers for each faculty, 91 questionnaires were returned back for analysis. The study findings indicated existence of a relationship between academic position, level of education and experience with linkages to the industry. Majority of the respondents still perceived the existence of barriers for the university - industry linkages such as too many bureaucracies for the link with the industry to take place that will eventually discourage them from making the next move, others cited difficulty faced by management of their faculties from knowing their true intention when engaging in the linkages, management might perceived them doing external works for extra income without any benefits to the university. Other barriers involved too many non-academic activities, mismanagement, miscommunication, leadership crisis, ethical problem, no suitable opportunity, too much paperwork and no clear direction of applied research, where most research is of little use to the industry and yet approved by the university. Further, lecturers are complacent with their environment, lack of top-down leadership and no understanding of better interactive of each different discipline.